A Technology-Supported Framework in Knowledge Sharing for Healthcare among Selected Cardiologists - Zaid A., Sabeeh (2019)
Knowledge sharing in healthcare industry impacts peoples’ lives and wellbeing therefore it ought to happen efficiently and uninterruptedly. The studied literature indicated the lack of comprehensive studies on the categories, assessments and characteristics of knowledge in organizations. Healthcare organizations were selected for the study context due to the crucial role of relevant knowledge in the delivery of quality healthcare services. The study of three models in knowledge management in the healthcare alongside the comprehensive literature on organizational knowledge has aided in realizing six focal themes. These themes and the shortcomings of the gap analysis of previous models assisted in shaping the conceptual Healthcare Knowledge Management Framework. The qualitative approach of in-depth interviews encompassing set of semi-structured questions was followed in this study. Eight specialized physicians were interviewed and their replies were analyzed qualitatively. Subsequently, data analysis produced several descriptive themes and codes. The following phase was the validation of the research design and the validation of the developed framework. A technological platform known as Knowledge Flow Tracer and Growth Analyzer (KFTGA) was implemented based on the developed framework. This platform aims to facilitate the knowledge-sharing activities among the community of physicians. For the purpose of KFTGA implementation, four medical experts participated in utilizing the tools’ features. Afterwards, forms with written interview questions were passed to the medical experts to capture their experience on utilizing the tool. Based on the developed framework, the eight interviewed healthcare specialists indicated their inclination to use technology as the main source of their learning and knowledge sharing. Four of those specialists expressed the relevance of the KFTGA platform for their knowledge-sharing needs and to facilitate top management launch of learning initiatives. Research findings indicated the suitability of the developed framework for knowledge management in its intended environment of operation in healthcare organizations. Additionally, the implementation of the technological platform by healthcare specialists have showed how technology can enable the learning and knowledge-sharing among communities of healthcare workers. Conclusions and recommendations for future studies were indicated at the end of this documentation for researchers who are interested in the same or similar research areas.